Late-Pleistocene rejuvenated volcanism and flank collapse deposits on a Cretaceous seamount near El Hierro, Canary Archipelago - Klügel, Andreas; Hauff, Folkmar; Beier, Christoph; Pfänder, Jörg A.; Freundt, Armin; Römer, Miriam; Schönhofen-Romer, Milena (Marine Geology, 2024)
Henry Seamount is a Cretaceous submarine volcano located 40 km southeast of El Hierro, the youngest of the Canary Islands, at 3700 m water depth. On the seamount's summit region, a widespread layer of heterolithologic volcaniclastic ash and lapilli beneath centimeters to decimeters of pelagic sediment was discovered and sampled during R/V Meteor cruise 146. The dominant lithology is a glassy basaltic ash that is depleted in highly incompatible elements and enriched in sulfur (S/K2O ratios of 0.10–0.20) compared to El Hierro lavas, suggesting an origin by a deep-sea volcanic eruption on Henry Seamount. Uranium-series disequilibria constrain the age of this ash to <350 ka, which implies rejuvenated volcanic activity of the seamount after up to 126 Ma of dormancy. This rejuvenated activity is possibly related to the Canary hotspot, where heating of lithosphere that had become amphibole-metasomatized during the formation of Henry Seamount led to renewed melt production. In contrast to the dominant ash type, most other volcaniclastic samples are geochemically indistinguishable from El Hierro lavas. The variety of lithologies, the angular to edge-rounded shapes of many fragments, and intimate mixture with the predominant ash suggest that this group of volcaniclastics was transported from El Hierro to Henry Seamount by a submarine debris avalanche and associated turbidity current. This implies a runup of up to 700 m even for centimeter-sized basaltic clasts after up to 40 km of lateral transport. Ar–Ar age constraints for two samples are ∼190–200 ka, which is consistent with the southeast-directed giant Las Playas II landslide from El Hierro as the most likely source. Henry Seamount thus provides a rare example where collapse-induced deposits from another volcanic edifice are found on top of a seamount and are mingled with ash to lapilli from previous rejuvenated volcanism. Mingling and reworking of the tephra may explain the lack of a discernible eruption center on top of the seamount.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Atlantic; Canary Islands; Flank collapse; Intraplate volcanism; Rejuvenated volcanism; Seamount